2013
DOI: 10.1002/hep.26615
|View full text |Cite
|
Sign up to set email alerts
|

Repopulation of the fibrotic/cirrhotic rat liver by transplanted hepatic stem/progenitor cells and mature hepatocytes

Abstract: Background & Aim Considerable progress has been made in developing anti-fibrotic agents and other strategies to treat liver fibrosis; however, significant long-term restoration of functional liver mass has not yet been achieved. Therefore, we investigated whether transplanted hepatic stem/progenitor cells can effectively repopulate the liver with advanced fibrosis/cirrhosis. Methods Stem/progenitor cells derived from fetal livers or mature hepatocytes from DPPIV+ F344 rats were transplanted into DPPIV− rats … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
58
0
2

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 68 publications
(66 citation statements)
references
References 46 publications
6
58
0
2
Order By: Relevance
“…34 Transplant of LSPCs from various sources has been accomplished via intrasplenic injection or infusion into a peripheral vein or the portal vein, with the idea that they may augment the impaired regeneration seen in the setting of chronic liver disease and promote reverse remodeling of fibrosis. 35 Engraftment and repopulation have been observed, even in the setting of fibrosis, 27,36 but generally, a regenerative stimulus such as partial hepatectomy or retrorsine injection is required for optimal engraftment. Although some studies suggest reduced fibrosis after LSPC transplant, 36 there have also been descriptions of a severe fibrogenic response that is, in fact, driven by the activation of the hepatic progenitor compartment.…”
Section: Liver Stem/progenitor Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…34 Transplant of LSPCs from various sources has been accomplished via intrasplenic injection or infusion into a peripheral vein or the portal vein, with the idea that they may augment the impaired regeneration seen in the setting of chronic liver disease and promote reverse remodeling of fibrosis. 35 Engraftment and repopulation have been observed, even in the setting of fibrosis, 27,36 but generally, a regenerative stimulus such as partial hepatectomy or retrorsine injection is required for optimal engraftment. Although some studies suggest reduced fibrosis after LSPC transplant, 36 there have also been descriptions of a severe fibrogenic response that is, in fact, driven by the activation of the hepatic progenitor compartment.…”
Section: Liver Stem/progenitor Cellsmentioning
confidence: 99%
“…35 Engraftment and repopulation have been observed, even in the setting of fibrosis, 27,36 but generally, a regenerative stimulus such as partial hepatectomy or retrorsine injection is required for optimal engraftment. Although some studies suggest reduced fibrosis after LSPC transplant, 36 there have also been descriptions of a severe fibrogenic response that is, in fact, driven by the activation of the hepatic progenitor compartment. 37 Furthermore, as in hepatocyte transplant, adult LSPCs are available only in limited numbers, and there are ethical constraints on the use of human fetal LSPCs.…”
Section: Liver Stem/progenitor Cellsmentioning
confidence: 99%
“…However, we recently demonstrated that the injury inherent in severe liver disease can also drive repopulation by transplanted cells without additional treatment. In these experiments, we studied advanced cirrhosis induced by the hepatotoxin thioacetamide (TAA) and observed engrafted and repopulating cell clusters at 2 months after transplantation without the additional stimulus of PH (13). …”
Section: Introductionmentioning
confidence: 99%
“…As in our previous studies (6, 13), the experiments utilized transplantation of dipeptidyl-peptidase IV-positive (DPPIV + ) donor cells into allogeneic DPPIV − host rats, but because BDL made the portal vein inaccessible, cell transplantation was carried out via intrasplenic injection. The experiments indeed demonstrated that biliary fibrosis induces hepatocyte repopulation, but surprisingly, they also showed striking and rapid transition of hepatocytes to cholangiocyte-like cells in both liver and spleen.…”
Section: Introductionmentioning
confidence: 99%
“…Entretanto como nos animais tratados houve uma maior expressão desse marcador, os resultados referentes e a morfometria e à quantificação demonstraram maior expressão deste marcador nos animais do grupo G3 em relação ao grupo G2, confirmando a hipótese de maior estimulo a regeneração tecidual, considerando o potencial regenerativo das células (PAYUSHINA et al, 2013;PATIL et al, 2014) As células derivadas do fígado embrionário de ratos com 14,5 dias de gestação demonstraram as características esperadas para terapia, uma vez que tais células apresentaram marcadores de células progenitoras hepáticas tais como CD 44, CD 117(c-kit), Nestin (OERTEL, 2011;BIN et al, 2012;EXPERIMENTAL, 2013;GONGH et al, 2013), assim como CK 18, marcador de hepatoblastos precursores de hepatócitos (FIEGEL et al, 2006;SEMERARO et al, 2012;HABEEB et al, 2015). Quanto ao marcador de colangiocitos, CK 7 (CANTZ; MANNS; OTT, 2008;OERTEL et al, 2008;GONGH et al, 2013), este também foi expresso, confirmando assim o seu bipotencial de diferenciação com sugerem os trabalhos de (OERTEL, 2011;BIN et al, 2012;YOVCHEV et al, 2014).…”
Section: Obtenção E Cultivo De Célulasunclassified